2022
DOI: 10.54099/jpma.v1i4.414
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Literasi Keuangan Islam Pada KSPPS di Kabupaten Jember

Abstract: Kehadiran KSPPS di Indonesia adalah salah satu perwujudan konsep keuangan yang sejalan dengan prinsip Islam sebagai agama mayoritas penduduk Indonesia sehingga memberikan banyak peluang bagi masyarakat dalam menjalankan bisnis atau usahanya. Masalah terbanyak yang muncul adalah tingkat literasi syariah dikalangan masyarakat Indonesia masih rendah. Tujuan utama pengabdian ini adalah memberikan edukasi dan pemahaman literasi keuangan Islam kepada para pengelola Koperasi Simpan Pinjam dan Pembiayaan Syariah (KSPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
3
0
5
Order By: Relevance
“…Proses pembelajaran harus dirancang, disusun, dan disesuaikan dengan keterampilan yang akan dicapai saat ini. Pemilihan pendekatan perlu menjadi fokus perhatian, dan disesuaikan dengan konsep kurikulum 2013 melalui pendekatan saintifik-tematik-holistik-integratif yang dapat dipadupadankan dengan pendekatan berbasis science (Amalia et al, 2022;Iskamto et al, 2022;Ningtyas & Wafiroh, 2022;Susriyanti et al, 2022;Tarigan et al, 2022).…”
Section: Pendahuluanunclassified
“…Proses pembelajaran harus dirancang, disusun, dan disesuaikan dengan keterampilan yang akan dicapai saat ini. Pemilihan pendekatan perlu menjadi fokus perhatian, dan disesuaikan dengan konsep kurikulum 2013 melalui pendekatan saintifik-tematik-holistik-integratif yang dapat dipadupadankan dengan pendekatan berbasis science (Amalia et al, 2022;Iskamto et al, 2022;Ningtyas & Wafiroh, 2022;Susriyanti et al, 2022;Tarigan et al, 2022).…”
Section: Pendahuluanunclassified
“…They must realize that a large income also comes with a high responsibility for their personal finances. High income by sailors must be properly managed so that in the future it can achieve financial well-being (Herispon et al, 2022;Iskamto et al, 2019;Kusumawati et al, 2023;Ningtyas & Wafiroh, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The biggest problem in Muslim-majority areas is that they are not interested in converting cooperatives into sharia cooperatives (Sabrina & Majid, 2019), from several studies based on the lack of application of education from an early age, regarding Islamic financial institutions and Islamic economic education among the community (Nuraulia, 2017), research results literacy about sharia microfinance is lacking, so sharia cooperatives are underdeveloped (Prihatini et al, 2022), as well as in debates about sharia cooperatives and sharia financial institutions at the Muslim community level, how are debates in Islamic economic law, so that the conflict escalates in accelerating the conversion of cooperatives into sharia cooperatives (Prawiro, 2016). Sholikhan (2022) from the results of his research, revealed that the slowdown in the conversion of Islamic cooperatives was found from a lack of evaluation from management and managers of the development of cooperatives, so that these operational problems delayed the conversion of cooperatives into Islamic cooperatives (Sholikhah, 2022).…”
Section: Introductionmentioning
confidence: 99%